Characteristics, treatment decisions and outcomes of prepubertal testicular germ cell tumor: A descriptive analysis from a large Chinese center. Issue 5 (October 2018) - Liu, P.; Li, W.; Song, H.C.; Jiao, L.L.; Zhang, W.P.; Sun, N.
Summary: Introduction: Prepubertal testicular tumors are fundamentally distinct from their postpubertal and adult counterparts. Racial and ethnic differences contribute to the incidence, characteristics, and histological distribution of prepubertal testicular germ cell tumors (PTGCTs). Objective: To elucidate the characteristics and treatment outcomes of PTGCTs in a Chinese cohort. Study design: Data were retrospectively reviewed from consecutive PTGCT patients aged <12 years who received treatment at the current institution from January 2007 to December 2015. Exclusion criteria were: patients aged >12 years, non-primary testicular germ cell tumors, and para-testicular tumors. Results: A total of 167 patients qualified for the study (Table ). The median age at diagnosis was 20 months (range 1–142). Pathology revealed 87 (50.9%) teratomas, 50 (29.2%) yolk sac tumors (YSTs), 33 (19.3%) epidermoid cysts, and one (0.6%) mixed germ cell tumor. Of the teratomas, 70 (80.5%) mature teratomas (MTs) and 17 (19.5%) immature teratomas (ITs) were detected. ITs manifested at a younger age and were larger in size compared with MTs ( P < 0.001). Testis-sparing surgery (TSS) was performed for all MTs and 10 ITs. Radical orchiectomy (RO) was performed for seven ITs. No metastatic or local recurrence was detected in benign tumors during follow-up. Obviously elevated alpha fetoprotein (AFP) levels were detected in all the YSTs. Of these, 47 (94%) were diagnosed as Stage I, one (2%) as Stage II, and two (4%) as Stage IV. After RO, recurrence was detected in one Stage I patient with a median follow-up of 46 months. One Stage II and two Stage IV patients died due to tumor progression. Discussion: Racial and ethnic differences were detected in PTGCTs. It is believed that the present study is the largest study detailing the clinicopathologic characteristics and treatment outcomes of PTGCTs in a Chinese cohort. Conclusions: Teratoma was the most common subtype of PTGCTs, followed by YST. ITs manifested as benign behavior and were more likely to be present at a younger age and have a larger tumor size compared with MTs. TSS was reliable for benign lesions. For Stage I YST, RO alone was valid. Salvage chemotherapy was effective and preventative retroperitoneal lymph node dissection may not be necessary for YST. The prognosis of PTGCTs was favorable.Summary Table. Pathological characteristics and treatment outcomes of prepubertal testicular germ cell tumors. Histologic Type No.(%) Age(mo), Median (range) Stage (No.) Initial surgery (No.) Adjuvant treatment (No.) Follow-up period (mo), Median (range) Recurrence/Metastasis Outcomes Teratoma 87 (50.9) 16 (9d–139) I (87) None 49.5 (20–125) None NED (74) Lost (13) Mature teratoma 70 20.5 (5–139) sTSS (70) 52.5 (20–125) Immature teratoma 17 5.0 (9d–12) 44.0 (20–115) G1 2 sTSS (2) G2 6 RIO (1) TSS (5) G3 9 RIO (6) TSS (3) Yolk sac tumor 50 (29.2) 15.5 (4–80) I (47) RIO (47) RPLND+PEB chemotherapy (1) 46 (19–121) RPLN(1) NED (44) Lost (3) II (1) RIO (1) Refused to chemotherapy (1) Lung (2) Died (1) IV (2) RIO (2) PEB chemotherapy (2) Brain (1) Died (2) Mixed germ cell tumor 1(0.6) 44 I (1) RIO (1) None 61 None NED (1) sTSS = scrotal testis-sparing surgery; RIO = radical inguinal orchiectomy; RPLND = retroperitoneal lymph node dissection; PEB = cisplatin, etoposide and bleomycin; NED = no exist of disease.